Faktor-Faktor Yang Mempengaruhi Minat Nasabah Dalam Menggunakan Mobile Banking Pada PT. Bank Syariah Indonesia, TBK KCP Stabat - Tessa Angelina (Al-Sharf: Jurnal Ekonomi Islam, 2022)
The research aims to find out the factors that affect customer interest in using mobile banking on PT. Bank Syariah Indonesia, Tbk KCP Stabat. The type of research conducted is quantitative research. This research data source was obtained from questionnaire answers given by research reponden, namely customers who use mobile banking services at PT. Bank Syariah Indonesia, Tbk KCP Stabat. The results showed that partial Security (X1) affected customer interest in using mobile banking (Y) in PT. Bank Syariah Indonesia, Tbk KCP Stabat. Partial Accuracy (X2) affects Customer Interests Using Mobile Banking (Y) on PT. Bank Syariah Indonesia, Tbk KCP Stabat. Simultaneously Security (X1) and Accuracy (X2) affect customer interest using Mobile Banking (Y) on PT. Bank Syariah Indonesia, Tbk KCP Stabat. Security (X1) and Accuracy (X2) affect Customer Interests Using Mobile Banking (Y) on PT. Bank Syariah indonesia, Tbk KCP Stabat by 74%. There is a positive or in line relationship between security and accuracy of customer interests using mobile banking at PT. Bank Syariah Indonesia, Tbk KCP Stabat.